The Effects of Local Labor Demand on Individual Labor Market Outcomes for Diffrerent Demographic Groups and the Poor - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1993)
Economists have traditionally had a keen interest in the effects of overall labor demand on the economic well-being of different population groups, particularly disadvantaged groups. The stronger the effects of overall demand on the economic well-being of the poor, the more support there is for boosting demand to "solve" poverty. But an alternative view is that the poor's problems have complicated social causes, and cannot be solved except by changes in social institutions. To put it plainly: are some people poor because the economy lacks jobs for them, or are these people poor because of something they lack? This debate has resurfaced in discussions of how to help the "underclass." Some researchers, such as William Julius Wilson (1987) and John Kasarda (1985, 1989, 1990), have attributed the growth of the underclass to the decline of central city manufacturing jobs. Other researchers, such as Lawrence Mead (1992), have attributed the growth of the underclass to cultural changes within the underclass community that have weakened the work ethic. The traditional view of economists was that aggregate economic demand has particularly strong benefits for disadvantaged groups such as the poor, the less educated, and blacks (Okun, 1973; Clark and Summers, 1981; Blank and Blinder, 1986; Blank, 1989). The benefits of aggregate growth for the poor seem to have weakened in the 1980s. Despite the long 1980s expansion, the income distribution has widened, and poverty has been little improved (Cutler and Katz, 1991; Blank, 1991). These 1980s problems for the poor are thought to be due to decreasing relative demand for unskilled workers, and a slowdown in the relative growth of college-educated versus less skilled workers (Bound and Johnson, 1992; Katz and Murphy, 1992). The evidence for this theory is mostly indirect. With only one time series on the U.S. macroeconomy as evidence, it is difficult to tell whether the effects of aggregate demand on poverty have really diminished. Because of the limited evidence in one time series of national data, some researchers have begun looking to local data to determine the effects of labor demand. The wide variety of demand conditions in local economies create a "natural laboratory" for determining the true effects of overall labor demand. These recent studies generally find that stronger local labor demand has significant benefits for the disadvantaged (Bartik, 1991a, 1991b, 1993; Freeman, 1989, 1991; Cain and Finnie, 1990). One implication of these findings is that national labor demand probably also has significant benefits for the disadvantaged. The effects of local labor demand are also of interest in their own right, and not just in what they might imply for national labor demand. Many local policies, such as local economic development policies, deliberately affect local growth. At the national level, the U.S. has generally not made significant efforts to intentionally alter the pattern of local and regional growth, but policies such as the interstate highway system probably have had important inadvertent effects on regional growth patterns. Other developed countries deliberately attempt to alter the pattern of local growth. If local demand conditions do have major effects on the disadvantaged, this raises the issue of whether some sort of national policy towards local and regional growth might plausibly be part of U.S. anti-poverty policy. The contribution of this paper is to use panel data on individuals (specifically, data from the Panel Survey on Income Dynamics) to examine how local demand conditions affect the economic well-being of disadvantaged groups and the poor. Previous research on local labor demand conditions uses data from a single cross-section of local economies, or a time-series of cross-sections of regions. With such data, estimated effects of local labor demand conditions on average labor market outcomes might be attributable to changes in local population composition, as we would expect local demand conditions to change in- and out-migration patterns. Because panel data follows the same individuals over time, it can address the important issue of whether local labor demand conditions affect specific individuals. This paper's estimates suggest that growth in the metropolitan economy particularly helps disadvantaged individuals. Local growth has stronger relative effects for males who are less educated, younger, or have lower expected earnings or work hours, and for females in poorer families. Local growth also has significant effects helping both males and females to exit from poverty, and helping prevent males and females from entering into poverty.
Additional information: A revised version of this paper appears as "The Distributional Effects of Local Labor Demand and Industrial Mix: Estimates Using Panel Data" in Journal of Urban Economics, Vol. 40, No. 2 (September 1996), pp. 150-178.
Keywords: R0; J4; 330; labor; demand; demographic; groups; poor; Bartik